7x2 -4x -5x2 +2x = 2x2 -2x
(2x+3)(2x+4)
Oh, dude, that's like basic math, right? So, 2x squared plus x squared is just 3x squared. It's like adding apples to apples, but with math. Easy peasy lemon squeezy!
It equals 53X- a number is squared when it is multiplied by itself, so 7X by 7X = 49X. 2X by 2X =4X, so 49X + 4X is 53X.
2x2 + 5x = x*(2x + 5)
-2(x + 5)(x - 6)
(x - 3)(2x + 7)
What do you mean "simplified"? It can definitely be factored.
(x + 4)(2x + 3)
(x - 4)(2x + 3)
-x2+2x
use the calculator
2x2 + 2x = 2x(x+1)
4
7x2 -4x -5x2 +2x = 2x2 -2x
(2x+3)(2x+4)
(2x+3)(x+3)